A case of extensive symptomatic lower limb heterotopic ossification in a boy (Medical Journal of Indonesia, 2019)
Heterotopic ossification refers to the abnormal growth of bone in the soft tissue. This report highlighted the case of heterotopic ossification in early childhood. A 3-year-old boy was presented with poor lower limb mobility and rigid left leg. At the age of 10 days, he developed a small lump as large as a quail egg in his left groin. Within 3 months, the lump grew bigger and spread to his leg and feet. His parents claimed no trauma history. It was confirmed by computed tomography scan which revealed multiple ossifications of the soft tissue infiltrating the lower limb muscles and infiltrating the skin, the pathological features showed hard mature trabeculated bone, mature fatty tissue, and loose connective tissue. The patient was treated with a series of soft tissue resections and was still under the care of surgeon with good prognosis.